Dark Patterns and Consumer Decision Making in Emerging Markets: Experimental Evidence from Indonesia - Uceng, Andi; Hanifah, Anisah Mutiara Zahra (Data : Journal of Information Systems and Management, 2024)
The rapid digitalization of Indonesia's economy has amplified concerns over deceptive interface designs known as dark patterns. These manipulative practices undermine user autonomy and raise legal and ethical questions. This study aims to provide experimental evidence specific to the Indonesian context, examining how four prevalent dark patterns urgency cues, drip pricing, consent manipulation, and fake social proof affect user trust, decision quality, and fairness perception within local e-commerce and fintech platforms. A between subjects experiment involving 300 participants was conducted using simulated Indonesian e commerce and fintech platforms. Participants were randomly assigned to one of five interface conditions: urgency, drip pricing, consent manipulation, fake social proof, or a neutral control. Behavioral metrics such as trust, regret, choice quality, and opt in rates were measured. Digital literacy was assessed as a moderating variable. All dark pattern treatments significantly reduced user trust and increased post decision regret compared to the control group. Drip pricing produced the highest regret and lowest fairness perception, while consent manipulation yielded inflated opt in rates. Low digital literacy was associated with greater susceptibility to deception and lower detection rates. These findings align with global behavioral research and highlight the vulnerability of digitally inexperienced users. Regulatory gaps were noted in Indonesia’s legal frameworks, which currently lack operational tools for addressing interface level manipulation. Dark patterns negatively impact consumer decision making and disproportionately affect vulnerable populations. Legal frameworks must evolve to explicitly define and penalize such designs. Promoting ethical UI practices and enhancing digital literacy are essential to safeguarding consumer rights and trust in Indonesia's digital economy.